Multiple, non-syndromic and non-metastatic pigmented basal cell carcinoma mimicking nodular melanoma: a rare presentation in Indian patient - Soni, Aum N.; Patel, Krina; Chauhan, Vasim (International Journal of Research in Dermatology, 2024)
Basal cell carcinoma is most common cutaneous malignancy having exposure to ultraviolet radiation as the most important predisposing factor. It could be solitary or multiple, in which case they can be associated with variety of syndromes. Out of various clinical types of BCC pigmented bcc can mimic sometimes malignant melanoma and in which case dermoscopy and skin biopsy can be helpful to differentiate. Metastasis of BCC is a rare phenomenon and it depends on various factors like tumour size, site, depth, histological type etc. Here we describe an interesting case of primary, non-syndromic, multifocal BCC which was initially diagnosed as melanoma but later on based on dermoscopy and histology diagnosed and successfully treated as BCC.